JNK Signaling Pathway Mediates Acetaminophen-Induced Hepatotoxicity Accompanied by Changes of Glutathione S-Transferase A1 Content and Expression - Shi, Chenxi; Hao, Beili; Yang, Yang; Muhammad, Ishfaq; Zhang, Yuanyuan; Chang, Yicong; Li, Ying; Li, Changwen; Li, Rui; Liu, Fangping (Frontiers in Pharmacology, 2019)
Acetaminophen (APAP) is an analgesic–antipyretic drug and widely used in clinics. Its overdose may cause serious liver damage. Here, we examined the mechanistic role of c-Jun N-terminal kinase (JNK) signaling pathway in liver injury induced by different doses of APAP. Male mice were treated with APAP (150 and 175 mg·kg−1), and meanwhile JNK inhibitor SP600125 was used to interfere APAP-induced liver damage. The results showed that JNK signaling pathway was activated by APAP in a dose-dependent manner. C-Jun N-terminal kinase inhibitor decreased JNK and c-Jun activation significantly (P < 0.01) at 175 mg·kg−1 APAP dose, and phosphorylation levels of upstream proteins of JNK were also decreased markedly (P < 0.05). In addition, serum aminotransferases activities and hepatic oxidative stress increased in a dose-dependent manner with APAP treatment, but the levels of aminotransferases and oxidative stress decreased in mice treated with JNK inhibitor, which implied that JNK inhibition ameliorated APAP-induced liver damage. It was observed that apoptosis was increased in APAP-induced liver injury, and SP600125 can attenuate apoptosis through the inhibition of JNK phosphorylation. Meanwhile, glutathione S-transferases A1 (GSTA1) content in serum was enhanced, while GSTA1 content and expression in liver reduced significantly with administration of APAP (150 and 175 mg·kg−1). After inhibiting JNK, GSTA1 content in serum decreased significantly (P < 0.01); meanwhile, GSTA1 content and expression in liver enhanced. These findings suggested that JNK signaling pathway mediated APAP-induced hepatic injury, which was accompanied by varying GSTA1 content and expression in liver and serum.